Cellular CARD11 Inhibits the Fusogenic Activity of Newcastle Disease Virus via CBM Signalosome-Mediated Furin Reduction in Chicken Fibroblasts - Wang, Wenbin; Wei, Qiaolin; Hao, Qiqi; Zhang, Yajie; Li, Yongshan; Bi, Youkun; Jin, Zhongyuan; Liu, Haijin; Liu, Xuelan; Yang, Zengqi; Xiao, Sa (Frontiers in Microbiology, 2021)
Newcastle disease virus (NDV) causes an infectious disease that poses a major threat to poultry health. Our previous study identified a chicken brain-specific caspase recruitment domain-containing protein 11 (CARD11) that was upregulated in chicken neurons and inhibited NDV replication. This raises the question of whether CARD11 plays a role in inhibiting viruses in nonneural cells. Here, chicken fibroblasts were used as a nonneural cell model to investigate the role. CARD11 expression was not significantly upregulated by either velogenic or lentogenic NDV infection in chicken fibroblasts. Viral replication was decreased in DF-1 cells stably overexpressing CARD11, while viral growth was significantly increased in the CARD11-knockdown DF-1 cell line. Moreover, CARD11 colocalized with the viral P protein and aggregated around the fibroblast nucleus, suggesting that an interaction existed between CARD11 and the viral P protein; this interaction was further examined by suppressing viral RNA polymerase activity by using a minigenome assay. Viral replication was inhibited by CARD11 in fibroblasts, and this result was consistent with our previous report in chicken neurons. Importantly, CARD11 was observed to reduce the syncytia induced by either velogenic virus infection or viral haemagglutinin-neuraminidase (HN) and F cotransfection in fibroblasts. We found that CARD11 inhibited the expression of the host protease furin, which is essential for cleavage of the viral F protein to trigger fusogenic activity. Furthermore, the CARD11-Bcl10-MALT1 (CBM) signalosome was found to suppress furin expression, which resulted in a reduction in the cleavage efficiency of the viral F protein to further inhibit viral syncytia. Taken together, our findings mainly demonstrated a novel CARD11 inhibitory mechanism for viral fusogenic activity in chicken fibroblasts, and this mechanism explains the antiviral roles of this molecule in NDV pathogenesis.